Situation of health, disability and substance abuse among women experiencing homelessness in Nicaragua - Berrios- Ballesteros, Alberto (2024)
Nicaragua is one of the lowest-income countries in Latin America. In Nicaragua there is no information available regarding women living homeless, and they are a particularly vulnerable group in situations of extreme poverty and social exclusion. This paper analyses health, disability and substance use in a sample of women living homeless (n=30) in the cities of León and Chinandega (Nicaragua). The women were asked to respond to a structured interview. The results show that women living homeless in Nicaragua presented a poor perception of their own health, high incidence of serious or chronic illness and high rates of disability. Alcohol and drug use (mainly inhaled glue) appeared mainly to affect younger women, largely during the period of slipping into homelessness. Major similarities were observed between women living homeless in low-income and high-income countries, despite being culturally very different. The lifestyle resulting from the adaptation to living on the street life subjects women living homeless to a rapid process of deterioration. Poor diet, lack of hygiene and barriers to accessing healthcare lead to a poor state of health, which appears to have had a significant impact on the length of time they remain homeless.